Bululngon kag Sumalayo case study of users of Ati medicine in Iloilo City. - Enano, Therese Victoria (UPHSI, 2017)
This research clarified the factors that influence the patronage of Ati products by the users living within Iloilo City. The factors show not only the social demographic of the users, but also their opinions on both the Ati and their medicine. The researchers aim to raise awareness of the experiences of the Ilonggos' use of the Ati medicine after having noticed a general lack of literature on the Negritos of the Philippines, specifically on the Ati. Intensive interviews and thematic analysis were used to conduct this research. The study made use of a compilation of recorded interviews with users of Ati medicine within Iloilo City; each session was transcribed, and analyzed according to similar themes within the respondents' statements. The researchers noted eight themes within the reasoning of the respondents, which were generalized to four factors that can influence the use of Ati medicine. This suggests that personal resources, external suggestion, impressions formed during use, and the Visayan dual belief system influence the inhabitants of Iloilo City who use Ati medicine.